5, 2 + 2, 4 3.7 + 6, 1 4.3 + 7.5 8 + 14, 6 3.75 - 2, 25 4, 65 - 3, 05 12, 69 - 10, 1 1 - 0.32 5, 8 + 9, 2 4, 9 + 6, 1 3.5 + 4.5 5.9 + 7 0, 8 - 0, 6 0, 9 - 0.5 6.5 - 0.4 5 - 0, 45 3, 5 + 7 8 + 2, 97 15 + 2, 08 0, 09 - 0, 03 0, 17 - 0, 02 0, 86 - 0, 46 3 - 0, 6 9 Ꭽ +
y=корень(1-4x)/x²; y=ln(x+корень(x^2+a)); y=sinx/(1+tgx); y=sin^4x +cos^4 x
Решение
y=корень(1-4x)/x²
y' = ((корень(1-4x))' *x^2 -корень(1-4x)*(x²)')/x^4 =
= ((1/2)*(1-4x)^(-1/2)*(-4)*x^2 -корень(1-4x)*2x)/x^4 =
=(-2x²/корень(1-4x) -2x*корень(1-4х))/x^4 =-2/(x²корень(1-4x)) -2корень(1-4х))/x^3
у=ln(x+корень(x^2+a))
y' = (ln(x+корень(x^2+a)))' = (1/(x+корень(x^2+a)))*(x+корень(x^2+a))'=
=(1/(x+корень(x^2+a)))*(1+(1/2)*(x^2+a)^(-1/2)*2x)=
=(1+x/корень(x^2+a))/(x+корень(x^2+a)) =
=( (x+корень(x^2+a))/корень(x^2+a))/(x+корень(x^2+a))=
= 1/корень(x^2+a)
y=sinx/(1+tgx);
y' = (sinx/(1+tgx))' = ((sinx)' *(1+tgx) - sinx*(1+tgx)')/(1+tgx)² =
= (cosx*(1+tgx) - sinx*(1/cos²x))/(1+tgx)²=
=(cosx + sinx - sinx/cos²x))/(1+tgx)²
(1+tgx)² =1+tg²x+2tgx =1/cos²x +2sinx/cosx =(1+sin(2x))/cos²x
(cosx + sinx - sinx/cos²x))/(1+tgx)² =
=(cosx + sinx - sinx/cos²x))/((1+sin(2x))/cos²x)=
=(cos³x+cos²x*sinx -sinx)/(1+sin(2x))
y=sin^4(x) +cos^4(x)
y' = (sin^4(x) +cos^4(x))' = 4sin³(x)*cos(x) +4cos³(x)*sin(x) =
= 4sin(x)*cos(x)(sin²(x) + cos²(x)) = 4sin(x)*cos(x) =2sin(2x)